2015
DOI: 10.1016/j.ijmultiphaseflow.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Monte-Carlo simulation of colliding particles or coalescing droplets transported by a turbulent flow in the framework of a joint fluid–particle pdf approach

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…Basically, particles transported by stationary homogeneous isotropic turbulence follow the Tchen-Hinze theory (Hinze 1972) that entails that the particle kinetic energy is directly linked to the fluid agitation (see for example Zaichik et al 2003;Fede and Simonin 2006) via fluid-particle v elocity c ovariance. H owever, L aviéville e t a l. (1997) and later Fede et al (2015) showed that when inter-particle collisions occur, particle agitation decreases even for elastic collisions. The way that electrostatic forces act on the particles is similar to collisions via the mechanism of Coulomb collisions typically found in cold plasma (Callen 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Basically, particles transported by stationary homogeneous isotropic turbulence follow the Tchen-Hinze theory (Hinze 1972) that entails that the particle kinetic energy is directly linked to the fluid agitation (see for example Zaichik et al 2003;Fede and Simonin 2006) via fluid-particle v elocity c ovariance. H owever, L aviéville e t a l. (1997) and later Fede et al (2015) showed that when inter-particle collisions occur, particle agitation decreases even for elastic collisions. The way that electrostatic forces act on the particles is similar to collisions via the mechanism of Coulomb collisions typically found in cold plasma (Callen 2003).…”
Section: Introductionmentioning
confidence: 97%
“…In such regions, the complex phenomenology of the flow prevents the use of simple SGS models to predict the effect of the unresolved flow scales on crucial phenomena such as dispersion, deposition and resuspension [98]. A common approach, valid also for RANS [30,83], has been to extend models developed for simpler, free-shear flows by incorporating the effect of near-wall gradients of turbulence intensity [81]. As we will try to highlight in the following, however, direct extensions not grounded on well-established first principles may easily produce poor results.…”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of numerical models have been developed to simulate aerosol dynamic processes including coagulation, nucleation, condensation, etc. [4,5].…”
Section: Introductionmentioning
confidence: 99%